Impact of IPM practices on microbial population and disease development in transplanted and direct-seeded rice - Khokhar, M. K.; Kumar, Rakesh; Kumar, Anoop; Sehgal, Mukesh; Singh, S. P.; Meena, P. N.; Singh, Niranjan; Acharya, L. K.; Birah, Ajanta; Singh, Kartar; Bana, R. S.; Gurjar, M. S.; et al. (Frontiers in Microbiology, 2024)
Integrated Pest Management (IPM) is a comprehensive approach to manage diseases, focusing on combining various strategies to reduce pathogen populations effectively and in an environmentally conscious way. We investigated the effects of IPM on beneficial microbial populations and its relationship with pathogen populations in both direct seeded rice (DSR) and transplanted rice (TR) systems. This study demonstrates that IPM practices have significantly higher populations of beneficial microbes, such as Trichoderma harzianum and Pseudomonas fluorescens, and lower levels of the pathogen Fusarium verticillioides, compared to non-IPM (Farmer practices'). The average mean population of T. harzianum was 6.38×10 3 CFU/g in IPM compared to 3.22 ×10 3 CFU/g in non-IPM during 2019 in TR at Bambawad. P. fluorescens mean population in 2019 was significantly higher in IPM (5.65×103 CFU/g) at than non-IPM (3.05×103 CFU/g) at Karnal location in DSR. The F. verticillioides population significantly lower in the IPM field (9.46 ×10 3 CFU/g) in comparison to non-IPM (11.48 ×10 3 CFU/g) during 2017 at Haridwar in TR. Over three years a significant increase in the populations of beneficial microbes in IPM plots was observed in all three location of both TR and DSR, highlighting the sustainable impact of IPM practices. Disease dynamics analysis revealed that IPM effectively managed key diseases in both DSR and TR systems, with significant correlations between microbial densities and diseases severity. A significant positive correlation was recorded between F. verticillioides population and bakanae incidence at all three locations. Sheath blight incidence was negatively correlated with P. fluorescens population in both TR and DSR. In DSR, bacterial blight and brown spot diseases are reduced with the increased population of T. harzianum. Bioagents T. harzianum and P. fluorescens reduced disease incidences, underscoring the role of beneficial microbes in disease suppression and their importance for sustainable production using IPM practices.